Tardigrade fauna of the South Sandwich Islands, maritime Antarctic - Mcinnes, Sandra J.; Convey, Peter (Zootaxa, 2005)
The maritime Antarctic South Sandwich Islands are an isolated oceanic archipelago of volcanic origin lying between 56º18’S, 27º34’W and 59º27’S, 27º22’W. All the islands are of recent origin (maximum ages 0.5–3 million years) with many still exhibiting some form of volcanic activity. The islands are part of the Scotia Arc, lying on a crustal upwarp extending from South Georgia through the South Sandwich Islands to the South Shetland Islands that connects the Andean chain of South America to the Antarctic Peninsula. As part of an extensive biological survey completed during early 1997, samples were collected from 10 of the 11 major islands in the archipelago from which the tardigrade fauna has subsequently been extracted. We report the composition of this fauna, and discuss its biogeographical relationships. Tardigrade species richness was low (6 taxa), in keeping with the recent formation and isolation of these islands. However, as reported previously for the terrestrial arthropod fauna and bryophyte flora, there is indication of both suband maritime Antarctic origin.